2021
DOI: 10.21203/rs.3.rs-1147096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Methylation Inhibitor 5-Aza-2′-Deoxycytidine Induces Genome-Wide Hypomethylation in Rice

Abstract: DNA methylation is a conserved epigenetic modification which is vital for regulating gene expression and maintaining genome stability in both mammals and plants. Homozygous mutation of rice methyltransferase 1 (met1) gene can cause host death in rice, making it difficult to obtain plant material needed for hypomethylation research. To circumvent this challenge, the methylation inhibitor, 5-Aza-2′-deoxycytidine (AzaD), is used as a cytosine nucleoside analogue to reduce genome wide hypomethylation and is widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For instance, in C. floridanus, worker larvae fed 5-Aza-dC exhibited both genome-wide hypomethylation and local-level egfr hypermethylation 30 . A hypermethylating effect of 5-Aza-dC was also reported in plants 50 . This inverse relationship is thought to be mediated by crosstalk with other epigenetic mechanisms, such as histone post-translational modifications 51 or non-coding RNAs 52 .…”
Section: Discussionmentioning
confidence: 65%
“…For instance, in C. floridanus, worker larvae fed 5-Aza-dC exhibited both genome-wide hypomethylation and local-level egfr hypermethylation 30 . A hypermethylating effect of 5-Aza-dC was also reported in plants 50 . This inverse relationship is thought to be mediated by crosstalk with other epigenetic mechanisms, such as histone post-translational modifications 51 or non-coding RNAs 52 .…”
Section: Discussionmentioning
confidence: 65%
“…5‐aza and hydroxyurea were used as hypo‐ or hyper‐methylating agents to study the relationship between SL and DNA methylation in a parasitic plant branched broomrape ( Phelipanche ramosa ) (Lechat et al, 2015). Liu et al (2022) examined the effects of 5‐aza‐2’‐deoxycytidine (AzaD) as a methylation inhibitor in rice and found that AzaD‐treated seedlings display similar CG hypomethylation and distribution with that of osmet1‐2 mutant. Interestingly, the application of 5‐aza increased the contents of tanshinones in Chinese sage ( Salvia miltiorrhiza ) (Yang et al, 2022a), highlighting the potential of using CREs in Chinese medicine to improve the contents of effective components.…”
Section: Chemical Genetics and Its Application To Epigenetics Studiesmentioning
confidence: 99%